In Vitro Inhibitory Activity of Corilagin and Punicalagin Against Toxoplasma gondii and Their Mechanism(s) of Action - Nicole T. Green-Ross; Homa Nath Sharma; Audrey Napier; Boakai K. Robertson; Robert L. Green; Daniel A. Abugri (Antibiotics)
Background/Objectives: Toxoplasmosis is a zoonotic disease caused by Toxoplasma gondii. The parasite infection in humans continues to rise due to an increasing seroprevalence rate in domestic and wild warm-blooded animals that serve as a major reservoir of the parasite. There are fewer drugs available for the treatment of toxoplasmosis. However, these drugs are limited in efficacy against tachyzoites and bradyzoites. Also, there are clinical side effects and geographical barriers to their use, especially in immunocompromised patients, children, and pregnant women. Tannins, a class of natural products, are known to have antimicrobial properties. However, little is known about the effects of Corilagin (CG) and Punicalagin (PU), which are classified as tannins, on T. gondii growth and their possible mechanism of action in vitro. We hypothesize that CG and PU could inhibit T. gondii growth in vitro and cause mitochondria membrane disruption via oxidative stress. Methods: Here, we investigated the anti-T. gondii activity of the two named tannins using a fluorescent-based reporter assay. Results: The 50% effective concentrations (EC50s) values for CG and PU that inhibited T. gondii parasites growth in vitro were determined to be 3.09 and 19.33 µM, respectively. Pyrimethamine (PY) was used as a standard control which gave an EC50 value of 0.25 µM. Interestingly, CG and PU were observed to cause high reactive oxygen species (ROS) and mitochondrial superoxide (MitoSOX) production in tachyzoites. This resulted in a strong mitochondria membrane potential (MMP) disruption in T. gondii tachyzoites. Conclusions: Therefore, the possible mechanism(s) of action of CG and PU against T. gondii is associated with the disruption of the mitochondria redox biology. Thus, the high ROS and MitoSOX produced as a result of these compounds created high oxidative stress, leading to mitochondrial dysfunction.